Generation of Renewable Power from Biodegradation of Anthracene in a Microbial Fuel Cell Reactor Using Different Bacterial Inocula - Alshehri, A.N.Z. (International Journal of Applied Sciences and Biotechnology, 2015)
Microbial fuel cells (MFCs) are increasingly attracting attention as a sustainable technology as they convert chemical energy in organic pollutants to renewable electricity. Anthracene is a polycyclic aromatic hydrocarbon (PAH) that presents a high pollution and health risk. In this study, anthracene degradation with electricity production in Single – chamber air cathode MFC was investigated with respect to values of its biodegradation and MFC performance using different inocula combinations (Anaerobic sludge (AS), Pseudomonas putida (PP), Geobacter sulfurreducens (GS), Shewanella putrefaciens(SP), mixed cultures, and combinations thereof). All the inocula showed high potentials for anthracene degradation efficiency and power density, ranged 41 – 98 % within 120 – 216h and 110.08 – 156.06 mW/m2, respectively. The best overall performing inoculum was anaerobic sludge supplemented with P. putida (AS+PP), having a degradation rate, degradation efficiency, COD removal, maximum power density and coulombic efficiency of 38 μM/d, 98 %, 83 %, 156.06 mW/m2 and 21, respectively. Effect of initial anthracene concentration was also investigated. Results indicated that increasing of initial anthracene concentration to 40 mg/L has a positive effect on both the anthracene degradation rate and the power density by 79 and 83.93 %, respectively, which attained by the best inoculum AS+PP (degradation rate of 41 μM/d and a maximum power density of 287.04 mW/m2).This study highlights the possibility of using MFCs technology to generate renewable electricity and achieve high degradation rates of anthracene simultaneously, through co-metabolism. Int J Appl Sci Biotechnol, Vol 3(2): 151-161 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12731